THE EFFECTIVENESS OF MUSIXMATCH APPLICATION INTEAM PAIR SOLO TECHNIQUE FOR TEACHING NARRATIVE WRITING - Pribadi, Wahyu Fahmi; Wahyuni, Sri; Yuliati, Yuliati (Universitas Negeri Semarang, 2017)
This paper presents the results of a quasi-experimental research aimed to find out whetherÂ Musixmatch and Team Pair Solo technique are effective for teaching narrative writing. There were 69 tenth grade students of a senior high school in Brebes, Central Java participating in this research. They were categorized into two groups named experimental and control group. To make it easier to understand, the result of this study is presented in the form of statistical data. The analysis result of the research showed that the use of Musixmatch and Team Pair Solo technique are more effective than the use of lecturing method for teaching narrative writing. This is shown by the post-test scores of the both groups, which was 81.74 for the experimental group and 77.00 for the control group. Furthermore, the result of Sig. (2-tailed) of T-test, which was 0.000,proved that there was a difference between students who were taught by using Musixmatch and Team Pair Solo technique and those who were taught by lecturing method.